Isaac Beeckman on matter and motion: mechanical philosophy in the making - Berkel, Klaas van (The Johns Hopkins University Press, 2013)
"Historians of science and the philosophy of science find the substance and stance of Isaac Beeckman's thought highly interesting, for it represented an early attempt to develop a comprehensive picture of the world by means of mechanistic theory, that is, forces acting upon one another. Besides possibly influencing Descartes, this view broke away from medieval religious assumptions and belief in occult forces. Berkel teases out Beeckman's evolving approach to nature by means of his extensive journals, explaining the leading concept of "picturability." Beeckman supplied a stepping stone (one still not widely appreciated) on the path that led to the scientific revolution"--